Analysis Of Financial Statements Quality Reviewed From Human Resources Competence, The Support 0f Top Management and The Use Of Information Technologies at Badan Pengelola Pajak dan Retribusi Daerah Kota Medan - Widopo Hanly; Rini Indahwati; Meily Surianti (Syntax Corporation, 2023)
The quality of financial reports in government is strongly influenced by the competence of goverment officials, Top management support and the use of information technology. Goverment officers are required to be able to make a positive contribution to all components of government, both the community, the private sector and other components, including the government agency itself. In the Minister of Finance Regulation 169/PMK.05/2018 concerning the Government Investment Accounting and Financial Reporting System and PP No. 71 of 2010 concerning on Government Accounting Standards, it states that the preparation of government financial reports has several requirements that must be acquired so that it could produce the good quality financial statements. The purpose of this study is to discover how the quality of financial reports in terms of human resource competence, top management support and the use of information technology at Badan Pengelola Pajak dan Retribusi Daerah Kota Medan using qualitative data analysis with in-depth interviews with key informants compiled using a google form questionnaire as a guide and analytical measuring tools in this study. The results showed that the three factors, namely top management support was found optimal, however, the competence of human resources, and the use of information technology had not been optimal, particularly in the quality of financial reports at Badan Pengelola Pajak dan Retribusi Daerah Kota Medan. (BPPRD Kota Medan).